Correlation between functional gastrointestinal disorders and gastric mucosa histopathology findings, including Helicobacter pylori infection, in Lima, Peru - McDonald, Katharine (2017)
Objective: This study aims to investigate the relationship between functional gastrointestinal disorders and histopathology characteristics, including H. pylori infection, of gastric mucosa, at Cayetano Heredia National Hospital, Lima-Peru, in 2013. Materials and methods: 112 patients were interviewed prospectively between June and July 2013 in the gastroenterology service. Dyspepsia, irritable bowel syndrome, and postprandial distress syndrome were characterized using the Rome III Survey. Results: Pathology results were determined by gastric biopsies obtained by endoscopy. Of the patients interviewed, biopsy results were obtained for 101. 22.8% had atrophy, 24.8% had intestinal metaplasia, 57.4% presented with H pylori. Conclusions: Using chisquare analysis, no statistically significant relationship could be identified between clinical presentation and biopsy results.